KEDUDUKAN DAN LOGIKA HUKUM PEMBUKTIAN PERCERAIAN BERDASARKAN STANDAR DURASI PISAH RUMAH DALAM SEMA NOMOR 3 TAHUN 2023 - Lisdayanti; Calvin; Hadi Putra Natanael Sitinjak; Agus Septima Ridwan (INTELIGENSIA MEDIA, 2026)
Marriage is a legal institution protected by the state through the principle of making divorce difficult as stipulated in Law Number 1 of 1974. The presence of Supreme Court Circular Letter Number 3 of 2023, which stipulates a minimum of six months of separation as a requirement for proving divorce, raises serious normative issues. This study examines the position of the Circular Letter of the Supreme Court (SEMA) in the hierarchy of laws and regulations and examines the consistency of the legal logic that supports it. The method used is normative juridical based on literature studies. The results of the analysis indicate that SEMA Number 3 of 2023 has exceeded its function as an internal technical guideline by adding material requirements not contained in Government Regulation Number 9 of 1975. The exception of domestic violence cases proves that the six-month standard is not an absolute and consistent measure. This study recommends a review of the substance of the SEMA to align with the open norm of Article 19 letter f of Government Regulation Number 9 of 1975.